Isolation and characterization of one autochthonous Beauveria sp. isolate from Cuban fields - Machin Suarez, A.; del Pozo Nunez, E. M.; Garcia Cruz, I; Hector Ardisana, E. F.; Dominguez, Y. [UNESP]; Guerrero-Morales, S.; Chavez Medina, J. A.; Escobedo Bonilla, C. M.; Perez-Alvarez, S. (Univ Sonora, 2022)
The genus Beauveria comprises a cosmopolitan teleomorphic and anamorphic group of entomopathogenic fungi. The aim of this study was to characterize a new isolate of Beauveria sp. and compare it to the LBB-1 commercial Cuban strain. The isolate was collected from ten individuals of the ant Atta insularis and ten adults of the coffee borer (Hypotenemus hampei). It was cultivated on solid SDAY medium enriched with 1% yeast extract. The biological effectiveness of the isolate was determined on C. formicarius. DNA was isolated using the CTAB method and the internal transcribed spacer region was amplified using the primers ITS1 and ITS 4. The consensus sequence obtained was deposited in GenBank (MK246940) and used for phylogenetic analysis. The isolate of Beauveria sp. showed differences in morphological characteristics; however, it showed low genetic variability regarding worldwide isolates of B. bassiana. Concerning its biological effectiveness, the isolate demonstrated to be virulent on the phytophagous adults, producing 50% mortality. Four clades were identified and the polytomous topology recovered for clade 1 indicates high genetic similarity (99-96%) with Beauveria bassiana from several countries. The morphological and molecular characterization made it possible to accurately identify the new isolate as Beauveria bassiana.
Keywords: Autochthonous isolate; entomopathogen; enzymatic activity; morphology; pest control